Evaluation of new suspension system for limb prosthetics - Gholizadeh, H.; Abu Osman, Noor Azuan; Eshraghi, A.; Ali, S.; Arifin, N.; Wan Abas, Wan Abu Bakar (BMC, 2014)
Background: Good prosthetic suspension system secures the residual limb inside the prosthetic socket and enables easy donning and doffing. This study aimed to introduce, evaluate and compare a newly designed prosthetic suspension system (HOLO) with the current suspension systems (suction, pin/lock and magnetic systems).Methods: All the suspension systems were tested (tensile testing machine) in terms of the degree of the shear strength and the patient's comfort. Nine transtibial amputees participated in this study. The patients were asked to use four different suspension systems. Afterwards, each participant completed a questionnaire for each system to evaluate their comfort. Furthermore, the systems were compared in terms of the cost.Results: The maximum tensile load that the new system could bear was 490 N (SD, 5.5) before the system failed. Pin/lock, magnetic and suction suspension systems could tolerate loads of580 N (SD, 8.5), 350.9 (SD, 7) and 310 N (SD, 8.4), respectively. Our subjects were satisfied with the new hook and loop system, particularly in terms of easy donning and doffing. Furthermore, the new system is considerably cheaper (35 times) than the current locking systems in the market.Conclusions: The new suspension system could successfully retain the prosthesis on the residual limb as a good alternative for lower limb amputees. In addition, the new system addresses some problems of the existing systems and is more cost effective than its counterparts. Â© 2014 Gholizadeh et al.; licensee BioMed Central Ltd.